2021
DOI: 10.1108/lht-04-2021-0122
|View full text |Cite
|
Sign up to set email alerts
|

User perceptions, academic library usage and social capital: a correlation analysis under COVID-19 after library renovation

Abstract: PurposeWhile the library has remained a preferred place of learning and received a positive perception in all aspects, the current space planning, as categorized in the “four-space model,” does not seem to address user needs well. The purpose of this article is to explore the correlations of user perceptions, academic library usage and social capital.Design/methodology/approachThis research presented a new approach to understanding the academic library's role by surveying 120 users about their preferred place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 40 publications
2
52
1
Order By: Relevance
“…Libraries are transforming from a space to store books into integrated cultural, meeting and learning spaces that tend to operate 24/7 (Yip et al , 2019; Chan et al , 2020a; Kim et al , 2020; Leung et al , 2022; Ho et al , 2022a,b; Jiang et al , 2022; Wong and Chiu, 2023). Noh (2022) investigated the library as a complex cultural space and showed that library users participated and enjoyed its services and programs.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…Libraries are transforming from a space to store books into integrated cultural, meeting and learning spaces that tend to operate 24/7 (Yip et al , 2019; Chan et al , 2020a; Kim et al , 2020; Leung et al , 2022; Ho et al , 2022a,b; Jiang et al , 2022; Wong and Chiu, 2023). Noh (2022) investigated the library as a complex cultural space and showed that library users participated and enjoyed its services and programs.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…In addition, due to the lockdown, most academic libraries were either closed or provided limited services. In this connection, Leung et al (2022) explored the correlations of user perceptions, academic library usage and social capital during this period. They noted that library users adjusted themselves to use these facilities with social distancing in their minds.…”
Section: Re-engineering In Learning and Library Services During The P...mentioning
confidence: 99%
“…Due to the recent lockdowns of COVID-19, many cultural venues such as museums and libraries have offered many new digital services and strengthened existing ones. Readers may also be interested in further recent developments in our articles (Leung et al , 2022a, b; Guo et al , 2021; Fasae et al , 2021; Meng et al , 2021, 2022; Yu et al , 2022b; Nadi-Ravandi and Batooli, 2022).…”
Section: Using Contemporary Technologies In Cultural Services Venuesmentioning
confidence: 99%
“…They noted that the decoupling of text they read and comments would lead users to mainly share text excerpts rather than original personal reactions to the story. Readers may note that social media has been important learning aid, especially for the younger generation, though it cannot replace formal learning (Li et al , 2021; Cheng et al , 2022; Leung et al , 2022a, b; Wang and Xie, 2022; Mak et al , 2022).…”
Section: Reading In the Mobile Agementioning
confidence: 99%